Agricultural waste-to-energy concerning a biofuel-fed molten carbonate fuel cell toward a novel trigeneration scheme; exergoeconomic/sustainability study and multi-objective optimization. (November 2022) - Li, Xiang; Wu, Junsong; Zhu, Xinyu; Liang, Huixing
Abstract: Attributable to the global upsurge in demand for agricultural products, agricultural energy needs are extending widely, while water and energy sources have been mitigated in recent years. This study focused upon bringing a proper solution to the mentioned discrepancy concerning the waste-to-energy concept. With this in mind, a gasification process for an agricultural waste, i.e., rice husk, is considered in this study for the simultaneous production of power, freshwater, and hydrogen to meet the agricultural needs. Meanwhile, a novel trigeneration scheme comprising a biofuel-fed molten carbonate fuel cell, a humidification/dehumidification-based desalination, and a solid oxide electrolyzer cell is designed and scrutinized from the exergoeconomic and sustainability standpoints. The sensitivity analysis is implemented at sole and dual parametric forms, where five decision-makings and six performance metrics are defined. Subsequently, a soft computing study through an artificial neural network is conducted to optimize the designed system utilizing the multi-objective grey wolf optimization method. Here, the objective functions are exergy destruction rate, sustainability index, and products' sum unit cost. The optimum electricity, freshwater, and hydrogen generation capacities are designated at 1442 kW, 4303 kg/h, and 51.51 kg/h. Besides, the aforementioned optimum objective functions are computed at 5084 kW, 0.0442 $/kWh, and 1.482, respectively.